(untitled) (PIONIR: JURNAL PENDIDIKAN, 2023)
Education is an effort to develop a nation to be better in order to create the formation of individuals who have an ethical and quality spirit. The quality of education starts from school, as formal education institutions for the community to improve the quality of education by applying the National Education Standards (NES). NES is a minimum requirement standard for the education system in all regions of Indonesia including content standards, assessment standards, management standards, financing standards, process standards, infrastructure standards, graduate competency standards, educators and education staff standards. This aim is to determine the success of implementing NES at Kampung Krueng Elementary School. This study uses a qualitative research method with a descriptive approach with primary data sources, namely observation and interviews, then secondary data is collected from reading books, journals, mass media and written documents. The results of the study show that several studies on the success of the NES scope have not been classified as effective and efficient because some standards have not been met, there are standards that already meet the NES well but need effort to be better such as the standards of educators and education staff during the teaching and learning process for students trying to bring a comfortable atmosphere so that students are enthusiastic about learning and those that are still not supportive, namely the standard of facilities and infrastructure which is still minimal in terms of budget and goods by the Department of Education. Keywords: Application, National Education Standards, Primary School